2012
DOI: 10.1016/j.ijar.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and inference with Conditional Gaussian Probabilistic Decision Graphs

Abstract: Probabilistic Decision Graphs (PDGs) are probabilistic graphical models that represent a factorisation of a discrete joint probability distribution using a "decision graph"-like structure over local marginal parameters. The structure of a PDG enables the model to capture some context specific independence relations that are not representable in the structure of more commonly used graphical models such as Bayesian networks and Markov networks. This sometimes makes operations in PDGs more efficient than in alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A convenient feature of PDGs is that any discrete BN can be transformed into a PDG (Jaeger, 2004). It is also known that CLG models can be represented as PDGs (Nielsen, Gámez, & Salmerón, 2012) and therefore inference on such hybrid models can be efficiently performed over them. Recently, it has been shown that MoTBFs can also be represented as PDGs, though so far they have only been tested in practice in supervised classification problems (Fernández, Rumí, del Sagrado, & Salmerón, 2014).…”
Section: Other Representationsmentioning
confidence: 99%
“…A convenient feature of PDGs is that any discrete BN can be transformed into a PDG (Jaeger, 2004). It is also known that CLG models can be represented as PDGs (Nielsen, Gámez, & Salmerón, 2012) and therefore inference on such hybrid models can be efficiently performed over them. Recently, it has been shown that MoTBFs can also be represented as PDGs, though so far they have only been tested in practice in supervised classification problems (Fernández, Rumí, del Sagrado, & Salmerón, 2014).…”
Section: Other Representationsmentioning
confidence: 99%